Metabolic Efficiency Improvement of Human Walking by Shoulder Stress Reduction through Load Transfer Backpack - Cao, Yu; Huang, Jian; Li, Xiaolong; Zhang, Mengshi; Xiong, Caihua; Mohammed, Samer; Zhu, Yaonan; Hasegawa, Yasuhisa (Proceedings of the ... IEEE/RSJ International Conference on Intelligent Robots and Systems, 2022)
The dynamic load attached to the load gravity imposes an excessive burden to human shoulders during load carriage, resulting in possible muscle injuries and additional physical exertion. This paper proposes an active suspension backpack, capable of transferring partial load from human shoulders to pelvis and alleviating the dynamic load through separated panels and motor actuation, to reduce pressure on human shoulders and improve walking metabolic efficiency. Based on the human body motion in the vertical direction, the dynamical model of the human-backpack system with shoulder interaction force measured by a soft ballonet with an embedded air pressure sensor is introduced, and an impedance controller has been implemented to maintain a relatively small and constant pressure on the shoulder. In an experimental case study, we presents preliminary results of three healthy subjects performing a treadmill walking with a 20kg load in ACTIVE configuration where the shoulder pressure shows a decrease by 30% along with a reduction of the metabolic energy consumption by 16.4%, compared with the load LOCKED case.